AKUNTABILITAS LEMBAGA PENGELOLA WAKAF: KAJIAN SHARIAH ENTERPRISE THEORY - Maggu, Istiqamah; Abdullah, Muhammad Wahyuddin; Muchlis, Syaiful (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract, Waqf possesses significant potential for sustainable development and community welfare. However, waqf management in Indonesia faces accountability challenges, resulting in low public trust and suboptimal asset utilization. Current accountability approaches remain primarily administrative, emphasizing formal compliance without fully reflecting Sharia values. This study analyzes Sharia Enterprise Theory (SET) in strengthening waqf institution accountability through a Systematic Literature Review of 12 articles from 2021–2025. Thematic analysis identifies conceptual developments, implementation practices, and SET challenges. Results show a paradigm shift from compliance-based to values-based approaches. SET provides a comprehensive framework integrating accountability to Allah, stakeholders, and trustworthy resource stewardship. Despite its relevance, SET implementation faces limitations including insufficient human resources, technology gaps, regulatory challenges, and organizational culture constraints. The study concludes that integrated efforts are essential through regulatory strengthening, nazhir capacity development, and technological support to achieve optimal implementation of SET in waqf institutions. Abstrak, Wakaf memiliki potensi besar untuk mendukung pembangunan berkelanjutan dan kesejahteraan masyarakat. Namun, pengelolaan wakaf di Indonesia menghadapi masalah akuntabilitas yang mengakibatkan rendahnya kepercayaan publik dan pemanfaatan aset wakaf yang belum optimal. Pendekatan akuntabilitas yang dominan masih bersifat administratif dan menekankan kepatuhan formal, tanpa sepenuhnya mencerminkan nilai-nilai syariah. Penelitian ini menganalisis peran Sharia Enterprise Theory (SET) dalam memperkuat akuntabilitas lembaga pengelola wakaf melalui Systematic Literature Review terhadap 12 artikel dari periode 2021–2025. Analisis tematik mengidentifikasi perkembangan konsep, praktik penerapan, dan tantangan implementasi SET. Hasil menunjukkan pergeseran dari pendekatan berbasis kepatuhan menuju pendekatan berbasis nilai. SET hadir sebagai kerangka komprehensif yang mengintegrasikan akuntabilitas kepada Allah, pemangku kepentingan, dan tanggung jawab pengelolaan sumber daya secara amanah. Meskipun relevan, implementasi SET terbatas oleh keterbatasan sumber daya manusia, teknologi, regulasi, dan budaya organisasi. Penelitian menyimpulkan diperlukan upaya terpadu melalui penguatan regulasi, peningkatan kapasitas nazhir, dan dukungan teknologi untuk implementasi optimal